Perancangan Logo Sebagai Visual Identity Kedai Kopi “OLSEN” Semarang - Frederik Prasidya Prakasita; Dwi Puji Prabowo; Agus Setiawan (Fakultas Ilmu Komputer Universitas Nahdlatul Ulama Sidoarjo, 2024)
“OLSEN” is a very new coffee shop in Semarang. This design aims to visualize the identity of the “OLSEN” coffee shop. The logo design is based on a unique selling proposition (USP), which is elaborated with the business development concept: a coffee shop with a family feel. In identifying the USP, the qualitative descriptive analysis method of strengths (S), weaknesses (W), opportunities (O), and threats (T) or SWOT is used. The data used is primary data collected through interviews and observations. Starting from the basis of the USP, the logo developed is a type of logotype with a choice of bold San Serif capital letters and an orange color choice. The logo is made minimalist to give a light, homey, and friendly impression. The logo is added with the slogan